Research Support as One of the Activity of a Scientific Library - O. L. Lavrik; T. A. Kalyuzhnaya (Библиосфера, 2022)
The purpose of the article is to present theoretical generalizations on library and information research as aspects of the development of information support for research and development: a classification of a complex of relevant works, products and services and a model that allows determining the level of development for each library based on its tasks and human resources. The methodological possibilities of the developed model are shown: it can be used for personnel training and for the organization of a new library at a research institute, research university under certain requirements.